Investigating the Impacts of Inquiry-Based Learning on Students' Understanding of Geographical Concepts - Yulianti, Temy (Future Space: Studies in Geo-Education, 2024)
The inherent complexity of geography is encapsulated within the comprehensive curriculum frameworks that guide instructional methodologies in senior high schools. This exploration delineates the pedagogical trajectory within a distinct context, namely Class X-1 Sosial Science at Madrasah Aliyah Negeri (MAN) 20 Jakarta, encompassing a diverse cohort of 36 students, comprised of 16 males and 20 females. The Kemmis McTaggart action research model was utilized to examine the effectiveness of an inquiry-based learning approach in augmenting students' conceptual grasp of the dynamics of the hydrosphere. Preliminary observations from cycles I and II indicate a noticeable enhancement in students' geographical conceptualization, particularly with respect to hydrospheric phenomena. Initial reticence observed during the initial exposure to inquiry-based modalities transitioned into increased engagement in subsequent iterations. This shift was significantly influenced by the gradual integration of argumentative discourse in the learning process, indicating a critical interplay between methodological familiarity and student activation. This investigation highlights the crucial role of customized pedagogical strategies in unravelling the intricate tapestry of geographical knowledge, thereby fostering an enriched educational environment conducive to both cognitive and experiential learning in the field of geography.